2009
DOI: 10.1080/00016480802251591
|View full text |Cite
|
Sign up to set email alerts
|

Increased expression of p63 and survivin in cholesteatomas

Abstract: Expression of p63 protein was diffusely observed in entire samples of cholesteatoma, especially in acquired cholesteatoma, compared with the control group. Congenital cholesteatoma showed variable p63 reactivity in a basal cell-like pattern. Primary and recurrent cholesteatomas showed no significant difference in p63 expression. Survivin was detected in 31 of 40 cholesteatoma samples. Acquired cholesteatomas showed especially increased survivin expression compared with congenital cases. The expression of p63 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
12
1
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 18 publications
3
12
1
1
Order By: Relevance
“…Park et al (18) determined that in cholesteatoma, survival is significantly increased; hence, apoptosis is suppressed in such cases. Olszewska et al (19) Turk Figure 4.…”
Section: Discussionmentioning
confidence: 99%
“…Park et al (18) determined that in cholesteatoma, survival is significantly increased; hence, apoptosis is suppressed in such cases. Olszewska et al (19) Turk Figure 4.…”
Section: Discussionmentioning
confidence: 99%
“…However, research using cell markers has confirmed that migration plays a role during normal or precholesteatoma conditions. 48 Other investigations have shown that metaplasia of mucosal epithelium into lightly keratinising squamous epithelium like masses can only be feasible in the absence of congenital remnants, skull trauma or previous middle-ear surgery. 56 Cholesteatoma pathogenesis: stepwise explanations Although different views on the migration, hyperplasia and metaplasia theories of acquired cholesteatoma formation have been expounded in the literature, it is conceivable that a combination of these theories may contribute to the pathogenesis of acquired cholesteatoma.…”
Section: Epidermal Hyperplasiamentioning
confidence: 99%
“…A variety of studies have attempted to differentiate the underlying pathogenesis and origin between congenital and acquired cholesteatomas [19,20] . It is known that, unlike in acquired cholesteatomas, bacterial infection is not involved in the development of the congenital type.…”
Section: Discussionmentioning
confidence: 99%